Dual Wavelength Chirped Pulse Regenerative Amplifier Based on Yb3+:LuAlO3 Crystal for Terahertz Applications - A. S. Rudenkov; V. E. Kisel; A. S. Yasukevich; K. L. Hovhannesyan; A. G. Petrosyan; N. V. Kuleshov (Приборы и методы измерений)
Compact diode-pumped chirped pulse regenerative amplifier systems with pulse repetition rate of hundreds kilohertz based on Yb3+-doped crystals are of practical importance for wide range of applications such as materials processing, medicine, scientific research, etc. The aim of this work was to study the Yb3+:LuAlO crystal based dual wavelength chirped pulse regenerative amplifier.Perovskite-like aluminate crystals have unique spectroscopic properties that allowed to use amplifier active element gain spectrum as an amplitude filter for amplified pulse spectrum and even obtained dual wavelength amplification without any additional components.In our work a simple way to obtain dual-wavelength operation of chirped pulse regenerative amplifier by using the active medium gain spectrum as an amplitude filter for the formation of the amplified pulses spectrum demonstrated for the first time to our knowledge. Maximum output power of 5.4 W of chirped pulses (3.8 W after compression) and optical-to-optical efficiency of 22.5 % have been obtained for Yb:LuAP E//b-polarization at 200 kHz repetition rate. Compressed amplified pulse duration was about 708 fs while separate spectral components durations were 643 fs and 536 fs at 1018.3 nm and 1041.1 nm central wavelengths, respectively. Performed investigations show high potential of Yb3+:LuAP crystals as active elements of compact diode pumped chirped pulse regenerative amplifiers